The Effect of Modified Constraint-Induced Movement Therapy on Upper Extremity Function of a Patient With Severe Acquired Brain Injury - Shiva Abedi; Nazila Akbarfahimi (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: This study aimed to investigate the effect of modified Constraint-Induced Movement Therapy (CIMT) on upper extremity function of a patient with severe Acquired Brain Injury (ABI). Materials & Methods: This study was conducted in 2017. The patient was a 33-year-old right-handed woman with a severe ABI admitted to Rofeideh Rehabilitation Center suffering from severe hypoxia due to suicide by hanging. She had no motion limitation, no history of dislocation or fracture, and no complaints of pain in the upper extremity, at the more involved side (left). The informed consent letter was obtained from the participant. The inclusion criteria for the subject were: active wrist extension of at least 20 degrees, maintaining balance for two minutes, Ashworth scale score <3, and mini-mental state examination score >24. The intervention was performed for two weeks, five days a week, three hours a day at Rofeideh Center. For the less affected upper limb, sling and mitt were used as constraints for at least six hours a day. We first used traditional techniques to reduce muscle tone (weight-bearing through upper extremity, trunk rotation, scapular protrusion, and reflex-inhibition pattern). Then, some selected motor tasks with shaping techniques were used. These tasks included cleaning the table with a towel, flipping the pages of a book, picking up the glass and carrying it to the mouth, picking up and moving a bottle, practicing to pick up and drop different objects, reaching arm forward to move objects from one place to another, counting with fingers, picking up and rotating a card, and doing fine exercises and fine motor and in-hand manipulation tasks by using coins and cereals. Assessments were performed at 4 stages of before, and then 2, 4, and 6 weeks after the intervention using Fugl-Meyer Assessment (FMA), Functional Independence Measure (FIM), Motor Activity Log (MAL), and Box and Block Test (BBT).  Results:‌ Improvement in the upper extremity function of a patient with chronic and severe ABI can be achieved by using the modified CIMT. According to FMA scores, an improvement was observed in four areas of motor function, balance, sensation, and range of motion. Its score increased from 24 at baseline to 56, two weeks after the intervention, and remained constant up to six weeks later. Also, manual dexterity under BBT was improved. Its score reached from 5 to 7, two weeks after, and 12, six weeks after the intervention. Moreover, the patient's FIM score improved from 19 to 36, two weeks after, and 38, six weeks after the intervention. Furthermore, regarding MAL results, the amount of movement score increased from 0 to 1.70, and the quality of movement score increased from 0 to 1.66, six weeks after the intervention.  Conclusion: Modified CIMT can be an effective method for improving the upper extremity function of patients with chronic and severe ABI in a short period.